Masters : gold: major works by leading artists - Hemachandra, Ray; Le Van, Marthe (New York : Lark Books, 2009)
Suitable for jewellers, metal smiths, collectors, and those who love beautiful workmanship, this title focuses on a topic - gold jewellery. It features 40 of the world's best goldsmiths and presents their finest pieces
Includes index
Keywords: Gold jewelry -- Design -- Catalogs; Gold jewelry -- History -- 21st century -- Catalogs